The Overview of Motivational Theories in Second Language Acquisition - Idaryani Nurdin; Fidyati Fidyati; Dewi Kumalasari; Rasyimah Rasyimah (Proceedings of AICS - Social Sciences, 2018)
This paper aims to review two motivational theories in second language acquisition, underlying on the effect of motivation to the students effort in learning English as foreign language and discussing the issues that emerge in applying motivational theories in English learning within global context. The paper begins by reviewing the development of motivational theories, previous and current trends, and debates on development of motivational theories. Its overview on theoretical developments is based on the examination of some published articles and books in motivation and the ﬁeld of language teaching. It is expected that this overview contribute positive future consideration for English teacher in developing teaching method that enables to motivate the student in learning English.Keywords:motivation, language learning, teaching method.